DEVELOPMENT AND VALIDATION OF A GRADIENT HPLC METHOD FOR QUANTIFICATION OF EDETATE DISODIUM IN LYOPHILIZED INJECTABLE DRUG PRODUCT - DESHPANDE, SHRIPAD; FAROOQUI, MAZAHAR; GANAP, GAJANAN; KHADKE, VISHAL; KAYANDE, D. D. (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present study was aimed to validate a developed reversed phase gradient high-performance liquid chromatography method for the quantitative determination of Edetate Disodium in the lyophilized injectable drug product. Methods: The amount of total Edetate disodium was analysed by HPLC assay using Edetate disodium USP as a reference standard. Injectable product was dissolved in acetone and Edetate disodium is separated out from API and then dissolved in water. Analysis was carried out using ferric chloride as a precolumn derivatizing reagent and YMC Pack ODS-A, 5 µm column with mobile phase as a mixture of tetrabutylammonium bromide buffer pH 2.8 and acetonitrile as the solvent, water used as diluent. The Edetate disodium quantified by U. V. wavelength at 254 nm. Results: The method was suitably validated with respect to specificity, linearity, precision, accuracy and solution stability, using this method the average recovery from spike sample is 98.2%, with a relative standard deviation of<3%. The minimal quantifiable level was 1.5 µg/ml. The results show that the procedure is accurate, precise and reproducible. Conclusion: In the present study an attempt has been made to develop and validate the analytical method for lyophilised injectable formulations and to generate the scientific database for formulation and evaluation of various lyophilised injectable containing Edetate disodium.